Fully solar-powered uninterrupted overall water-splitting systems - Zhang, Qichong (2020)
Extensive research efforts have been recently devoted to the development of self‐driven electrocatalytic water‐splitting systems to generate clean hydrogen chemical fuels. Currently, self‐driven electrocatalytic water‐splitting devices are powered by solar cells, which operate intermittently, or by aqueous batteries, which deliver stored electric power, leading to high operating costs and environmental pollution. Thus, a fully solar‐powered uninterrupted overall water‐splitting system is greatly desirable. Here, the solar cells, stable output voltage of 1.75 V Ni–Zn batteries, and high efficiency zinc–nickel–cobalt phosphide electrocatalysts are successfully assembled together to create a 24 h overall water‐splitting system. Specifically, the silicon‐based solar cells enable the charging of aqueous Ni–Zn batteries for energy storage as well as providing sufficient energy for electrocatalysis throughout the day; in addition, the high‐capacity Ni–Zn batteries offer a steady output voltage for overall water‐splitting at night. Such an uninterrupted solar‐to‐hydrogen system opens up exciting opportunities for the development and applications of renewable energy.